Enhancing Orang Asli awareness and empowerment through an intervention program / Rohaida Nordin ... [et al.] - Nordin, Rohaida; Hassan@Yahya, Muhamad Sayuti; Shapie, Rohimi; Jalil, Faridah; Matthew, Albert Witbrodt (2014)
This paper discusses the initiative of a group of students and lecturers at the Faculty of Law, UKM in enhancing awareness and empowerment of the indigenous peoples of Malaysia, the Orang Asli through an Intervention Programme. The main objective of the Intervention Programme is to identify the problem and difficulties that the Temuans at Rancangan Penempatan Semula (RPS) Sungai Bilut have encountered due to their relocation after their ancestral land is reclaimed by the government for the Kelau Dam project. Firstly, the programme looks at negative impact of the relocation and seeks a viable area of improvement for Orang Asli to have a decent social and economic opportunities and a standard of living that will be at par with other citizen of the country. Secondly, it carries out Intervention Programme based on transfer of knowledge method in order to strengthen awareness and empowerment amongst the said Orang Asli. The ultimate objective of the programme is to generate human resource among the said Orang Asli that help the community to solve their problem and difficulties with special focus to the rights of livelihood and decent work, protection of women and child, and relationship between the Orang Asli and NGOs and Human Rights Commission. The Intervention Programme at RPS Sungai Bilut is only the beginning of an effort in enhancing awareness and empowerment of the Orang Asli. There will still be a need for special initiatives and programme to implement the suggestions made at national level for the realisation of the rights of Orang Asli‟s in general.